The Effect of Implementing Corporate Governance and Human Resources Competence On Financial Lacks - Yosefin, Yosefin (Devotion : Journal of Research and Community Service, 2022)
Companies need to make efforts to organize the company to avoid a decline in the company's financial condition which causes bankruptcy, including the implementation of Good Corporate Governance and the existence of qualified human resource competencies in the company. This study aims to determine the effect of implementing good corporate governance and human resource competence on financial lacks. This study uses a quantitative research method with a descriptive approach. Data collection techniques in this study used questionnaires and literature studies. The research data were then analyzed using the SPSS program. The results of the study show that the implementation of good corporate governance has a negative effect on financial lacks and the competence of human resources has a negative effect on financial lacks